Konsep Pendidikan Anak Perspektif Zakiah Daradjat Dan Relevansinya Dengan Tujuan Pendidikan Islam - Nurul Hakim; Susi Fitriana (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
Child education holds a major influence on the child's future. Today, many children who are damaged morally even have many problems in the world of child education. As a result children deviate even fall into criminal acts. To foster children's education in the aspects of family, school and society it is important for educators to introduce these three aspects. In introducing these three aspects, there must have been a lot of thoughts of figures discussing children's education, one of which was Zakiah Daradjat. Zakiah Daradjat is the only thinker who instills the concept of education based on Islamic scholarship on children's education in families, schools and communities. He is a female figure in Indonesia who has put a lot of attention in various fields including education, morals, the lives of children, youth, teachers, families and schools. The results of this discussion are (1) the concept of children's education in the family aspect perspective Zakiah Daradjat includes parents to be role models for children, cultivation of soul and taqwa given to children, (2) the concept of child education in the school aspect perspective Zakiah Daradjat includes mental, moral guidance , religious education conducted intensively and talent then fosters children's intelligence, (3) relevance of the concept of child education in family aspects and school aspects of perspective Zakiah Daradjat with the aim of Islamic education in the family aspect is the experience received by children, in the aspect of school, namely intelligence, whereas in the aspect of society namely the achievement of education in a real society.